(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to identify the prevalence and factors associated with the need for removable prostheses in the elderly Brazilian population. In addition, its impact on eating difficulties and self-perceived oral health was determined. Methodology: This cross-sectional, population-based study used data from the last National Health Survey (NHS) carried out in Brazil. Chi-square test was used to initially analyze the data, followed by multiple Poisson regression to obtain adjusted prevalence ratios. Results: A total of 11,697 elderly people were included, of whom 90.8% needed removable prostheses. Complete dentures were needed in 40.9% of participants, while partial dentures were needed by 49.9%. The elderly who were older (p=0.001), had grayish-brown complexion (p=0.004), a low level of education (p<0.001), and multiple chronic diseases (p<0.001) had a greater need for removable prostheses. Successively, this need had an impact on poor self-perceived oral health (p<0.001) and greater difficulties in eating (p<0.001). Conclusion: The need for a removable prosthesis is associated with worse socioeconomic and health conditions. In addition, it has a negative impact on self-perceived oral health and feeding.